Hybrid Energy to Drive Renewable Energy Diversity in Bibliometric Analysis - Sarjana, Sri; Widokarti, Joko Rizkie; Fachri, Helman; Pranita, Diaz (International Journal of Energy Economics and Policy, 2022)
Hybrid energy is a combination of two or more energy sources, some of which can be sourced from several renewable energies combined, or combined with fossil energy. Renewable energy diversity is implemented through the development of hybrid energy in order to obtain new energy sources that are more effective and efficient. Bibliometric analysis is directed to analyze topics that have novelty according to the time period of publication based on qualitative methods. Analysis of scientific literature sourced from scientific journals published in the last ten years with the topic of hybrid energy. The results of study stated that several topics that had novelty were obtained to be used in the development of further knowledge and technology, especially in the development of hybrid energy including energy density, renewable energy system, supercapacitor, storage system, algorithm, electric vehicle, and energy system. The development of hybrid energy is very important to be followed up in order to get more comprehensive source of energy diversity and has full support for development of green technology that has relevance in sustainable development.